Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $p$ be a prime. Prove that $p$ divides $ab^p−ba^p$ for all integers $a$ and $b$.

(This is not a homework)

share|improve this question
    
Hint: It helps to think of it as $ab^p \equiv ba^p \mod p$. –  Tara B Mar 24 '12 at 12:47
    
Oh, I see that while I was laboriously typing my comment on an iPad, people provided actual answers. Oh well. –  Tara B Mar 24 '12 at 12:49
1  
The variant of Fermat's Theorem that says $x^p\equiv x\pmod{p}$ makes this automatic. –  André Nicolas Mar 24 '12 at 16:54
add comment

4 Answers 4

KV Raman's answer is quite right, but I'll write my answer anyway because I find it tidier.

$\mathbb{Z}_p^* = \mathbb{Z}_p\setminus \{0\}$ is a cyclic group of order $p-1$ under multiplication, so $a^{p-1} \equiv 1 \mod p$ for all integers not divisible by $p$. If $a$ is divisible by $p$, then $a^n \equiv 0 \mod p$ for all $n$. So we have $a^p \equiv a \mod p$ for $a\in \mathbb{Z}$. (This is Fermat's Little Theorem.)

Now for any integers $a$ and $b$, \[ ab^p \equiv ab \equiv a^pb \mod p \] and so $ab^p - ba^p \equiv 0 \mod p$, which means $p$ divides $ab^p - ba^p$.

share|improve this answer
    
You got my vote +1 for your proof Tara. –  Kirthi Raman Mar 24 '12 at 13:19
1  
+1. That's much easier than arranging things such that the $a^{p-1}$ form of Fermat's little theorem applies directly. –  Henning Makholm Mar 24 '12 at 13:21
add comment
up vote 12 down vote accepted

$$ab^p-ba^p = ab(b^{p-1}-a^{p-1})$$

If $p|ab$, then $p|(ab^p-ba^p)$ and also if $p \nmid ab$, then gcd$(p,a)=$gcd$(p,b)=1, \Rightarrow b^{p-1} \equiv a^{p-1} \equiv 1\pmod{p}$ (by Fermat's little theorem).

This further implies that $\displaystyle{p|(b^{p-1}-a^{p-1}) \Rightarrow p|(ab^p-ba^p)}$.

Q.E.D.

share|improve this answer
add comment

Hint $\ $ little Fermat $\rm\Rightarrow mod\ p\!:\ n^p \equiv n\ \Rightarrow\ f(a,b^p)\equiv f(a,b)\equiv f(a^p,b)\ $ for all $\rm\:f\in \mathbb Z[x,y]$

share|improve this answer
add comment

Hint

Fermat's Little Theorem

share|improve this answer
    
@Downvoter Will the downvoter please explain? –  user21436 Mar 30 '12 at 15:02
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.